Organophosphorus flame retardants and phthalate esters in indoor dust from different microenvironments: Bioaccessibility and risk assessment. (May 2016) - He, Ruiwen; Li, Yunzi; Xiang, Ping; Li, Chao; Zhou, Chunyang; Zhang, Shujun; Cui, Xinyi; Ma, Lena Q.
Abstract: Incidental ingestion of indoor dust is an important pathway for human exposure to organophosphorus flame retardants (OPFRs) and phthalate esters (PAEs). However, little is known about their bioaccessibility in indoor dust. In this study, indoor dust samples were collected from houses, offices, public microenvironments (PMEs), and university dorms, and physiologically based extraction test (PBET) was used to measure the bioaccessibility of OPFRs and PAEs in these dust samples. Total concentrations of OPFRs in dust samples ranged from 0.01 to 63.2 μg g −1, with significantly lower concentrations in dorm dust (median = 0.30 μg g −1 ) than those in houses (3.12), offices (5.94), and PMEs (11.6). Total PAEs ranged from 5.49 to 2161 μg g −1 with significantly lower concentrations in dorm dust (379 μg g −1 ) than those in the other three types of dust (767, 515, and 731 μg g −1 ). When subject to PBET, the bioaccessibility of OPFRs ranged from 8.18% (triphenyl phosphate) to 54.5% (Tris(2-chloroisopropyl) phosphate) for OPFRs, and from 1.21% (di-2-ethylhexyl phthalate, DEHP) to 81.1% (dimethyl phthalate) for PAEs. Estimated exposure doses for adults and infants to OPFRs via dust ingestion were much lower than the reference doses (RfD), but intake dose of DEHP for infants was higher than the RfD of 20 μg kg −1  d −1 . However, the DEHP intake dose did not exceed the RfD after incorporating bioaccessibility into risk assessment. Our data indicated the importance of considering contaminant bioaccessibility during risk assessment of indoor dust. Highlights: Indoor dust was collected from house, office, dorm, public microenvironments (PME). OPFRs/PAEs were 0.01–63.2/5.49–2161  μg g −1 with the lowest levels in dorm dust. Bioaccessibility was 8.18–54.5%/1.21–81.1% for OPFRs/PAEs. No compound pose risk higher than reference dose if considering bioaccessibility.